(M)asking the landscape and body-scape in South Africa: The Well Worn theatre company and site-specific theatre. Issue 3 (1st September 2015) - Jacobs, Tristan
By focusing on the use of body and ensemble in performance practice, this article aims to draw links between site-specific theatre, the neutral mask, sustainability and the work of the Johannesburg-based Well Worn theatre company, established in 2008. Using performance and play as an activist tool to examine, interpret and discuss the most pressing eco-social themes of our time, Well Worn creates the space and conditions necessary for critical thinking and open dialogue. The company devises physical and visual theatre work for crafting a poetic and meaningful connection between audience, subject-matter and play. Essentially, the company is committed to acting imaginatively to address and reflect on issues of eco-socialism, climate justice and earth-consciousness, thus placing more emphasis on that ancestral act of monitoring ourselves and our communities. As a case-study, Well Worn theatre company – particularly the Baobab Project – provides an area of focus for our considerations of embodied heritage as well as how the efficacy of mask-work and site-specific theatre breaks the boundaries (and theatrical conventions) with regard to framing culture.